1975
DOI: 10.1159/000193656
|View full text |Cite
|
Sign up to set email alerts
|

Regional and Total Lung Function Studies in Patients with Hemidiaphragmatic Paralysis

Abstract: Global and regional lung function were studied in 17 subjects with hemidiaphragmatic paralysis. Global lung function (VC, MVV, and FEV1) in the sitting position was reduced by an average of about 25 %. Regional lung function data in the same position showed a considerable decrease in perfusion (19%), ventilation (20%), and lung volume (7%) of the diseased side as compared to reference values obtained in healthy volunteers. Compared to the partition of function in the supine, the perfusion of the affected lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…Arborelius et al (1975) showed the reduction to be least prominent supine and greatest sitting. However, the reduction in perfusion (19%) and ventilation (20%) in the sitting posture tended to be better matched than in the supine posture when perfusion was reduced by 9% and ventilation by 14%.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Arborelius et al (1975) showed the reduction to be least prominent supine and greatest sitting. However, the reduction in perfusion (19%) and ventilation (20%) in the sitting posture tended to be better matched than in the supine posture when perfusion was reduced by 9% and ventilation by 14%.…”
Section: Discussionmentioning
confidence: 97%
“…Orthopnoea is a prominent symptom in many patients with diaphragmatic paralysis (McCredie et al, 1962) and hypoxia has also been observed in these patients when recumbent (Arborelius et al, 1975). We have examined airway closure in relation to this hypoxia and also studied the positional changes in overall lung function in hemidiaphragmatic paralysis unassociated with intrathoracic disease.…”
mentioning
confidence: 99%
“…These patients were free of symptoms. Arborelius et al (1975) studied 17 patients with a paralysed hemidiaphragm and found a mean vital capacity in the sitting position of 74-6% predicted and total lung capacity of 86-1 % predicted; however, in more than half these patients the paralysis had followed thoracotomy.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution in the opposite lung did not differ significantly from that found in normal subjects although the proportion of inhaled xenon reaching the lung base was rather less than in the normal group. The washout of injected xenon was norinal except for slight impairment at the lung base on the paralysed side in one patient and at both bases in another.So far as we are aware, the only previous account of regional lung function in diaphragmatic paralysis is the recent report by Arborelius, Lilja, and Senyk (1975). These authors studied 17 patients in various postures.…”
mentioning
confidence: 99%
See 1 more Smart Citation